2006
DOI: 10.1002/ajh.20800
|View full text |Cite
|
Sign up to set email alerts
|

Estimated glomerular filtration rate in sickle cell anemia is associated with polymorphisms of bone morphogenetic protein receptor 1B

Abstract: Renal disease is common in sickle cell anemia. In this exploratory work, we used data from a longitudinal study of the natural history of sickle cell disease to examine the hypothesis that polymorphisms (SNPs) in selected candidate genes are associated with glomerular filtration rate (GFR). DNA samples and clinical and laboratory data were available for 1,140 patients with sickle cell anemia. GFR was estimated using the Cockcroft-Gault and Schwartz formulas for adults and children, respectively. We examined *1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 40 publications
(41 reference statements)
1
28
1
Order By: Relevance
“…However, no SNP tested was associated with the MTD HbF, indicating that these recently elucidated regulators of HbF are probably not critical for the HbF response to hydroxyurea beyond their baseline effects. Two SNPs in ARG1 and ARG2, respectively, were associated with the HbF change, but no pathophysiologic mechanism is clear at this time; however, the rs2295644 marking the ARG2 gene locus was associated with the MRTinf (P ϭ .008) and has been previously implicated in renal disease, 38 so it could potentially affect renal clearance of the drug, the AUC, and possibly the MTD dose. In contrast, after adjustment for FDR, no SNPs were predictive of For personal use only.…”
Section: Discussionmentioning
confidence: 94%
“…However, no SNP tested was associated with the MTD HbF, indicating that these recently elucidated regulators of HbF are probably not critical for the HbF response to hydroxyurea beyond their baseline effects. Two SNPs in ARG1 and ARG2, respectively, were associated with the HbF change, but no pathophysiologic mechanism is clear at this time; however, the rs2295644 marking the ARG2 gene locus was associated with the MRTinf (P ϭ .008) and has been previously implicated in renal disease, 38 so it could potentially affect renal clearance of the drug, the AUC, and possibly the MTD dose. In contrast, after adjustment for FDR, no SNPs were predictive of For personal use only.…”
Section: Discussionmentioning
confidence: 94%
“…Variants in BMPR1B (rs2240036, rs4145993, rs17022863, rs1434549, rs1470409, rs4331783) and MYH9 (rs5756129, rs11912763, rs16996648, rs5750248, rs1557529, rs5756152, rs8141189, rs1005570. rs16996672, rs933224) that had been previously identified in the literature as being associated with sickle cell nephropathy 16,17 were also examined for associations with eGFR and urine albumin concentrations, respectively. The imputation qualities for BMPRIB and MYH9 are provided in Online Supplementary Table S1. HMOX1 and SOD2 were candidate genes identified as having differential expression from the PCR experiments.…”
Section: Genotyping In the Uic And Walk-phasst Cohortsmentioning
confidence: 99%
“…The first identified four variants and three haplotypes in BMPR1B, a bone morphogenetic protein receptor gene, which were associated with estimated glomerular filtration rate (eGFR). 16 The second found that individuals with the APOL1 G1/G2 risk variants (defined as being homozygous or compound heterozygous for the G1 and/or G2 risk variants using a recessive model) were 3.4-times more likely to have dipstick-defined proteinuria and that variants in MYH9 were independently associated with proteinuria after adjusting for APOL1 variant status. 17 Furthermore, a significant interaction between the APOL1 G1/G2 risk variants and an MYH9 risk haplotype was observed in predicting eGFR.…”
Section: Introductionmentioning
confidence: 99%
“…The TGF-b/BMP pathway is a key driving force in the pathogenesis of chronic kidney scarring, and single-nucleotide polymorphisms in genes related to this pathway have been implicated in SCN. 7 A recent single study suggested that the MYH9-APOL1 locus, an important genetic risk . Panels A-C were taken on an Olympus BX50 microscope using an Olympus DP12 camera and Olympus image software (Melville, NY).…”
Section: Natural History Epidemiology and Genetic Modifiersmentioning
confidence: 99%